Adolescents with Sport-Related Concussion Who Adhere to Aerobic Exercise Prescriptions Recover Faster. Issue 9 (28th September 2022) - CHIZUK, HALEY M.; WILLER, BARRY S.; CUNNINGHAM, ADAM; BEZHERANO, ITAI; STOREY, EILEEN; MASTER, CHRISTINA; MANNIX, REBEKAH; WIEBE, DOUG J.; GRADY, MATTHEW F.; MEEHAN, WILLIAM P.; LEDDY, JOHN J.; HAIDER, MOHAMMAD N.
ABSTRACT: Purpose: There is growing evidence that subsymptom threshold aerobic exercise speeds recovery from sport-related concussion (SRC). It is not known whether there is a direct relationship between adherence to a personalized exercise prescription and recovery or if initial symptom burden affects adherence to the prescription. Methods: This study was a planned secondary analysis of one arm of a randomized controlled trial. Male and female adolescent athletes (age 13–18 yr) presenting within 10 d of SRC were given aerobic exercise prescriptions based on their heart rate threshold at the point of exercise intolerance on a graded treadmill test. Adherence was determined objectively with HR monitors and compared against time to recovery. Participants who completed at least two-thirds of their aerobic exercise prescription were considered to be adherent. Results: Sixty-one percent of adolescents met the adherence criterion. Those who were adherent were more symptomatic and were more exercise intolerant at their initial visit, yet they recovered faster than those who were not adherent (median recovery time, 12 (interquartile range, 9–22) d vs 21.5 (interquartile range, 13–29.8) d; P = 0.016). On linear regression, adherence during week 1 was inversely related to recovery time ( β = −0.002 (−0.003, 0.0), P = 0.046) and to initial exercise tolerance ( β = −0.886 (−1.385, −0.387), P < 0.001), but not to initial symptom severity ( β = 0.545 (−0.232, 1.323), P = 0.146). No adverse events or near misses were reported. Conclusions: Adherence to individualized subsymptom threshold aerobic exercise within the first week of evaluation is associated with faster recovery from SRC. The data suggest that initial degree of exercise intolerance, but not initial symptom severity, affects adherence to aerobic exercise prescribed to adolescents within 10 d of SRC.